ANALYSIS OF THE GENEROSITY OF SPANISH PENSIONS (2010-2020) - Acosta-Rosero, David (Economic Annals, 2025)
This paper shows the impact of the legislative changes that increased the statutory retirement age and the number of contributing years on the generosity of the public pension scheme in Spain between 2010 and 2020. To do so, it was necessary to find a way to measure the generosity of the Spanish public pension programme. The methodology provided by Scruggs (2014), which in turn is a further development of that created by Esping-Andersen (1993), allows for the classification of different Welfare States based on their generosity. This article uses this method to quantify the public pension scheme during the observed period of time and then compare it against hypothetical data where legislative interventions that directly affected the variable data would not have taken place. The results show a clear quantifiable impact of the law over the generosity of the protection programme. However, the overall trend present in the index was not created by the legislative changes, it was only exacerbated by them.